Comment on 'Relativistic extension of shape-invariant potentials' - Castro, Antonio S. de [UNESP] (IOP Publishing, 2002)
This comment criticizes the recently published approach of Alhaidari for solving relativistic problems. It is shown that his gauge considerations are inaccurate and that the class of exactly solvable relativistic problems is not as large as the author claims.